2018
DOI: 10.2147/cmar.s167863
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of differentially expressed circRNAs in esophageal and breast cancer

Abstract: IntroductionCircular RNAs (circRNAs) function as efficient microRNA sponges with gene-regulatory potential and are promising cancer biomarkers. In this study, we used the Arraystar Human circRNA Array to construct a genome-wide circRNA profile of esophageal squamous cell cancer (ESCC) and breast cancer (BC).Patients and methodsExpression levels between cancer lesions and adjacent normal-appearing tissues were compared. We observed 469 upregulated circRNAs and 275 downregulated circRNAs in ESCC. Hsa_circRNA_103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Recently, accumulating evidence has indicated that circRNAs could function as a biomarker to predict the clinical severity in cancer patients [17][18][19][20]. Previously, circ_0005230 was found upregulated in BC tissues revealed by the human circRNA microarray [13]. However, its expression profiles in BC cells, clinical features, biological functions, and mechanisms were not explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating evidence has indicated that circRNAs could function as a biomarker to predict the clinical severity in cancer patients [17][18][19][20]. Previously, circ_0005230 was found upregulated in BC tissues revealed by the human circRNA microarray [13]. However, its expression profiles in BC cells, clinical features, biological functions, and mechanisms were not explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Shi et al reported that circ_0005230 expression was dramatically elevated in four paired BC tissue samples relative to their corresponding normal tissue samples screened by circRNA microarray [13]. Circ_0005230 was spliced from DNM3OS (DNM3 opposite strand/antisense RNA) gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research regarding circRNAs in BC is just beginning. Previous study uncovered that circ_0103552 level was significantly boosted in tissue specimens compared to the noncancerous tissue samples proved by circRNA microarray . circ_0103552 is a circRNA mapped to chr15:43294752‐43314999 in human genome.…”
Section: Introductionmentioning
confidence: 99%
“…1 With the rapid development of high-throughput sequencing technology and bioinformatics, accumulating evidence has demonstrated that ncRNAs are involved in the pathophysiology of various diseases, including Alzheimer's disease, 2 cardiovascular disease, 3 and cancers. [4][5][6][7][8] Abundant and functionally important types of ncRNAs include Dovepress Dovepress 1998 song et al tRNAs, rRNAs, miRNAs, siRNAs, lncRNAs, circRNAs, etc. ncRNAs play an important role in the epigenetic regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we had a great interest in a candidate circRNA (hsa_circ_0000337, also known as hsa_cir-cRNA_100872) in ESCC, which was identified through a high-throughput Arraystar Human circRNA Microarray. 8 hsa_circ_0000337 was one of the top ten upregulated cir-cRNAs with a fold change (FC) =6.255 and P=0.006. To evaluate the feasibility of hsa_circ_0000337 as a diagnostic biomarker and therapeutic target, we verified its expression in ESCC tissues and cell lines and explored the functions of this specific circRNA in vitro by Cell Counting Kit-8 (CCK-8), colony formation, wound healing, and Transwell assays.…”
Section: Introductionmentioning
confidence: 99%